2013
DOI: 10.5172/conu.2013.2527
|View full text |Cite
|
Sign up to set email alerts
|

Do practice nurses have the knowledge to provide diabetes self-management education?

Abstract: Purpose: Practice nurses are ideally positioned to provide key aspects of self-management education to a large majority of people with diabetes within a primary care setting. However, practice nurses have seldom had comprehensive training in this field and consequently their role may have limitations. A study was designed to determine the diabetes related knowledge levels of practice nurses in a regional/rural setting in Australia. Methods: A cross-sectional study was undertaken using a questionnaire to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, a previous study showed that health education programmes that provide traditional advice have a success rate of only 5%e10% [3]. Therefore, effective new approaches to helping patients improve their self-management abilities are urgently needed.…”
Section: Introductionmentioning
confidence: 98%
“…However, a previous study showed that health education programmes that provide traditional advice have a success rate of only 5%e10% [3]. Therefore, effective new approaches to helping patients improve their self-management abilities are urgently needed.…”
Section: Introductionmentioning
confidence: 98%
“…28,29 There is also a need for continuing professional development of practice nurses, especially in dietary assessment and advice, and intensification of medication management. 23,30 However, the six studies we identified in which practice nurses had an enhanced role in T2D management and received specific training showed mixed results, with improvements in some but not all parameters.…”
Section: Discussionmentioning
confidence: 96%
“…The teach-back method is an evidence-based method that confirms patient understanding of materials taught to them by a health care professional (Tamura-Lis, 2013). Nurses working in long-term care have a variety of educational backgrounds and may not have been educated on the teach-back method (Hollis et al, 2014). The teachback method has been utilized in acute care but there was very little evidence found supporting the use of this method in long-term care.…”
Section: Discussionmentioning
confidence: 99%